Program Aplikasi Persediaan Barang Dagang Berbasis WEB Pada PT. Padu Perkasa Nusantara - Siti Nurbaiti; Yakub (LPPM STMIK AL MUSLIM, 2024)
The constraints found in the process of entering and leaving goods at PT. Padu Perkasa Nusantara is still done manually, so when the warehouse admin is asked to see the stock of goods, which ends up taking quite a long time to prepare and the level of stock adjustment is high because there is no synchronization of goods data with physical stock. In terms of inventory accounting, it is also not possible to know the nominal amount of existing inventory so that it can be monitored to maintain the cash flow balance of the stock. This research was made with the final results of the inventory application program using the FIFO method using the waterfall method with PHP and MySQL database which can control requests according to FIFO principles and control the amount of stock in the warehouse, so that every request is always based on the amount of stock available. With this inventory information system, problems related to requests according to the FIFO principle can be carried out and stock data can be viewed at any time and can be controlled, especially from the inventory accounting side. The process of making stock reports and reports of goods receipts and expenditures becomes more efficient because they can be printed based on a certain time period. Keywords: fifo, inventory accounting, inventory, inventory, php, mysql